PERAN GURU DALAM MEMBENTUK KARAKTER SISWA DI SD NEGERI 05 SALIDO KECIL - Putri, Nevi Marsalia; Efendi, Rinja (STKIP Pesisir Selatan, 2025)
Education is not only aimed at transferring knowledge from teachers to students, but also focuses on forming superior student character, both in terms of knowledge, attitude, and skills.Character education is a primary focus in today's education system, particularly given the challenges of globalization and rapid social change. The role of teachers is crucial in shaping students' character. Teachers are not only responsible for delivering academic material. This study aims to describe the role of theachers in shapping student’ character at sd negeri 05 salido kecil. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The result of the study indicate that teachers play an important role in character building through exemplery behavior, habituation, integration of character values into learning, end cooperation were successfully instilled theroug various planned strategies. Althoug there are several obstacles such as family bakground and external influences, reachers continue to strive to create a supportive educational enviroment for character development.